ANALISIS TATA KELOLA DAN RISIKO TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 5 DOMAIN EDM03 DAN APO12 - Risma Fauziah; Laura Egidia; Maftri Fatun; Arum Pujiwinarni; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study analyzes the implementation of IT governance and IT risk management at Rumah ITSHOP Purwokerto using the COBIT 5 framework focusing on the EDM03 and APO12 domains. A descriptive qualitative method was applied through interviews, observations, and documentation. The result show that ITSHOP has implemented basic controls such as daily data backups, access restrictions, data encryption, and periodic security audits, however risk management practices are not yet formally documented. The maturity level indicates Level 3 (Established Process) reflecting consistent processes that require further echancement through formal policies, documentation, and measurable risk indicators.